Controlled Human Malaria Infection (CHMI) differentially affects cell-mediated and antibody responses to CSP and AMA1 induced by adenovirus vaccines with and without DNA-priming - Sedegah, Martha (Hum Vaccin Immunother, 2015)
We have previously shown that a DNA-prime followed by an adenovirus-5 boost vaccine containing CSP and AMA1 (DNA/Ad) successfully protected 4 of 15 subjects to controlled human malaria infection (CHMI). However, the adenovirus-5 vaccine alone (AdCA) failed to induce protection despite eliciting cellular responses that were often higher than those induced by DNA/Ad. Here we determined the effect of CHMI on pre-CHMI cellular and antibody responses against CSP and AMA1 expressed as fold-changes in activities. Generally, in the DNA/Ad trial, CHMI caused pre-CHMI ELISpot IFN-γ and CD8+ T cell IFN-γ responses of the protected subjects to fall but among non-protected subjects, CHMI caused rises of pre-CHMI ELISpot IFN-γ but falls of CD8+ T cell IFN-γ responses. In contrast in the AdCA trial, CHMI caused both pre-CHMI ELISpot IFN-γ and CD8+ T cell IFN-γ responses of the AdCA subjects to fall. We suggest that the falls in activities are due to migration of peripheral CD8+ T cells to the liver in response to developing liver stage parasites, and this fall, in the DNA/Ad trial, is masked in ELISpot responses of the non-protected subjects by rises in other immune cell types. In addition, CHMI caused falls in antibody activities of protected subjects, but rises in non-protected subjects in both trials to CSP, and dramatically in the AdCA trial to AMA1, reaching 380 μg/ml that is probably due to boosting by transient blood stage infection before chloroquine treatment. Taken together, these results further define differences in cellular responses between DNA/Ad and AdCA trials, and suggest that natural transmission may boost responses induced by these malaria vaccines especially when protection is not achieved.